‘’Influence of Reciprocation vs Continuous Rotation on Coronal and Apical Root Canal Sealing Using Two Different Sealers: An in Vitro Study’’ (Journal of Hama University, 2019)
The aim of this study is to determine the influence of some shaping and obturation variables on coronal and apical root canal sealing.The sample include 52 single root and canal teeth which are uniformed in length to 16 mm from the apex and divided into 4 experimental groups (n=10 teeth each) according to the preparetion system and the sealer used, as follows: (group #1: continuous rotaion/ZOE, group #2: continuous rotaion/ADSEAL, group #3: reciprocation/ZOE, group #4: reciprocation/ ADSEAL). In addition, 2 control groups (n=6 each). The external root surface is painted with two layers of nail polish except the most apical 2mm. The apical part is immersed in blue methylene for 24 hours, the coronal part is immersed in red eucine for 24 hours. The apical and coronal sealing was measured by stereo microscope after making longitudinal sections. The data obtained is statistically analyzed using T student for independent means test. The results show that reciprocation provides more coronal sealing than continuous rotaion. Also, ADSEAL provides more coronal and apical sealing than ZOE. (P